Solid electrolyte compounded mixed ion conductor material as well as preparation method and application thereof
By introducing hydrophobic groups-containing surfactants into the electrolyte of solid lithium metal batteries and compounding them with CNTs, mixed ion conductor materials are prepared, which solves the battery safety problems caused by lithium dendrites, and realizes a lithium-ion secondary battery with high safety, high energy density and long life.
Patent Information
- Application Number
- CN202311379828.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-24
- Publication Date
- 2025-04-25
AI Technical Summary
Solid-state lithium metal batteries are prone to growth of lithium dendrites under high current density, resulting in battery safety problems and short circuits. It is difficult for the existing technology to effectively solve this problem.
Mixed ionic conductor materials are prepared by introducing hydrophobic groups into the solid electrolyte for modification and composited with carbon nanotubes (CNTs) to improve the conductivity and safety of the battery.
This method effectively inhibits the formation of lithium dendrites, improves the safety and energy density of the battery, extends the battery life, and improves the Coulomb efficiency and cycle life of all-solid-state lithium batteries.
Smart Images

Figure CN119890420A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a solid electrolyte composite mixed ion conductor material and a preparation method and application thereof. Background Art
[0002] Although lithium-ion batteries with graphite anodes have been the popular battery chemistry for decades, battery applications continue to expand and evolve. These new technologies require batteries with higher capacity, specific energy and energy density, and improved safety that cannot be achieved with traditional lithium-ion batteries. This drives the development of next-generation batteries that can better meet the battery needs of new and future technologies.
[0003] The development of solid-state lithium metal batteries is one of the ways. Although solid-state lithium metal batteries can guarantee a specific energy of more than 500Whkg -1 and energy density greater than 1000WhL -1 , but lithium dendrite growth remains a concern, especially when high current densities are used. As the demand for fast charging grows, safe operation at high current densities will become more critical. However, lithium dendrites are a common problem in lithium-ion batteries. They are branch-like structures that grow during the charge and discharge process and can cause short circuits and safety issues in the battery. As long as lithium metal is used in the battery, dendritic growth seems likely to occur.
[0004] To this end, the present inventors have conducted extensive work to modify the solid electrolyte to minimize dendritic growth and allow operation at higher current densities, thereby obtaining lithium-ion secondary batteries with high safety, high energy density and long life. Summary of the invention
[0005] The purpose of the present invention is to provide a mixed ion conductor material of a solid electrolyte composite and a preparation method and application thereof. The mixed ion conductor material is obtained by modifying the solid electrolyte with a surfactant containing a hydrophobic group and then compounding it with CNTs, so that it can be used to prepare a secondary battery with high safety, high energy density and long life.
[0006] To this end, in a first aspect, an embodiment of the present invention provides a method for preparing a solid electrolyte composite mixed ion conductor material, comprising:
[0007] In a liquid phase dispersion system, a surfactant containing a hydrophobic group and solid electrolyte powder particles are dispersed, the solid electrolyte powder particles are modified by the surfactant containing a hydrophobic group, and the modified solid electrolyte particles are obtained after drying;
[0008] The modified solid electrolyte particles and carbon nanotubes (CNTs) are dispersed by ultrasonic stirring in a liquid phase dispersion system to obtain a composite product;
[0009] The composite product is dried to obtain the solid electrolyte composite mixed ion conductor material.
[0010] Preferably, the mass ratio of the solid electrolyte powder particles to the surfactant is 99:1-85:15;
[0011] The mass ratio of the solid electrolyte powder particles to the CNTs is 50:50-1:99.
[0012] Preferably, the dispersion speed of the dispersion treatment is 1000-3000 rpm, the dispersion time is 0.5-4 h, the drying temperature is 90-200° C., and the moisture content after drying is less than 5000 ppm.
[0013] Preferably, the frequency of the ultrasound is 1-100 kHz, the stirring speed is 5 rpm-50 rpm, and the time is 0.5 hour-5.0 hours.
[0014] Preferably, the solid electrolyte powder particles are crystalline materials containing lithium or sodium, and the particle size is between 10nm-1um.
[0015] Preferably, the solid electrolyte powder particles specifically include: lithium lanthanum zirconium oxide, lithium lanthanum niobium oxide, lithium lanthanum tantalum oxide, lithium titanium silicate, lithium aluminum titanium phosphate, lithium lanthanum titanium oxide, lithium aluminum titanium oxide, lithium zirconium phosphate, lithium zinc phosphate, lithium calcium tannin oxide, lithium zirconium silicate, sodium zirconium silicon phosphorus oxide, sodium iron copper manganese oxide, β-aluminum oxide or a mixture of one or more thereof;
[0016] The surfactant containing a hydrophobic group specifically includes: sodium tridecyl sulfosuccinate, polyoxyethylene oleate, hydroxyethyl ether cellulose, octadecylamine, sodium dodecyl sulfate, dodecylamine, sodium dodecylbenzene sulfonate, siloxane coupling agent, phthalate coupling agent, aluminate coupling agent, metal composite coupling agent, phosphate coupling agent, borate coupling agent, etc., including alkane groups, cycloalkane groups, aromatic hydrocarbon groups, fatty acid groups, polyoxypropylene groups, and one or more mixtures of coupling agents.
[0017] Preferably, in the liquid phase dispersion system, the dispersion liquid is a mixture of one or more of deionized water, N-methylpyrrolidone, alcohol, dimethylformamide, ethyl acetate, and isopropanol.
[0018] Preferably, the CNTs include single-arm CNTs and multi-arm CNTs, or a mixture of both.
[0019] In a second aspect, an embodiment of the present invention provides a solid electrolyte composite mixed ion conductor material prepared by the preparation method described in the first aspect above.
[0020] In a third aspect, an embodiment of the present invention provides a lithium-ion battery comprising the solid electrolyte composite mixed ion conductor material described in the second aspect above.
[0021] The preparation method of the mixed ion conductor material of the solid electrolyte composite provided by the embodiment of the present invention, by using a surfactant containing a hydrophobic group, the hydrophobic group interacts with the surface of the solid electrolyte particles to reduce the surface tension of the interface, they can improve the compatibility between the components, help disperse the solid electrolyte particles, reduce the agglomeration and accumulation of the particles, and help prepare a uniform mixed material. In addition, the hydrophobic group can also improve the interaction between the solid electrolyte particles and the carbon nanotubes, and promote their dispersion in the liquid phase. By compounding with carbon nanotubes (CNTs), the conductivity of the battery can be enhanced, and a high-strength and chemically stable support is provided at the same time. The present invention prepares a mixed ion conductor material that can conduct both ions and electrons. The mixed ion conductor material can help inhibit the formation of lithium dendrites, because this material has both ionic conductivity and electronic conductivity, which makes the current distribution inside the battery more uniform, reduces the formation of dendrites and the problems caused by the uneven current inside the battery, thereby ensuring the safe operation of high-capacity lithium batteries, thereby improving the coulombic efficiency and cycle life of all-solid-state lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 A flow chart of a method for preparing a solid electrolyte composite mixed ion conductor material provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0023] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.
[0024] The present invention provides a method for preparing a solid electrolyte composite mixed ion conductor material, the main steps are as follows: Figure 1 As shown, including:
[0025] Step 110, in a liquid phase dispersion system, a surfactant containing a hydrophobic group and solid electrolyte powder particles are dispersed, the solid electrolyte powder particles are modified by the surfactant containing a hydrophobic group, and the modified solid electrolyte particles are obtained after drying.
[0026] Among them, the solid electrolyte powder particles are crystalline materials containing lithium or sodium, and the particle size is between 10nm-1um. The solid electrolyte powder particles specifically include: lithium lanthanum zirconium oxide, lithium lanthanum niobium oxide, lithium lanthanum tantalum oxide, lithium titanium silicate, lithium aluminum titanium phosphate, lithium lanthanum titanium oxide, lithium aluminum titanium oxide, lithium zirconium phosphate, lithium zinc phosphate, lithium calcium tan oxide, lithium zirconium silicate, sodium zirconium silicon phosphorus oxide, sodium iron copper manganese oxide, and β-alumina.
[0027] Surfactants containing hydrophobic groups specifically include: sodium tridecyl sulfosuccinate, polyoxyethylene oleate, hydroxyethyl ether cellulose, octadecylamine, sodium dodecyl sulfate, dodecylamine, sodium dodecylbenzene sulfonate, siloxane coupling agents, phthalate coupling agents, aluminate coupling agents, metal composite coupling agents, phosphate coupling agents, borate coupling agents, etc., including alkane groups, cycloalkane groups, aromatic hydrocarbon groups, fatty acid groups, polyoxypropylene groups, and one or more mixtures of coupling agents.
[0028] The mass ratio of the solid electrolyte powder particles to the surfactant is 99:1-85:15.
[0029] The dispersion speed of the dispersion treatment is 1000-3000rpm, the dispersion time is 0.5-4h, the drying temperature is 90-200℃, and the moisture content after drying is less than 5000ppm.
[0030] In the liquid phase dispersion system, the dispersion liquid is a mixture of one or more of deionized water, N-methylpyrrolidone, alcohol, dimethylformamide, ethyl acetate, and isopropanol.
[0031] Step 120, dispersing the modified solid electrolyte particles and carbon nanotubes CNTs in a liquid phase dispersion system by ultrasonic stirring to obtain a composite product;
[0032] The CNTs include single-arm CNTs and multi-arm CNTs, or a mixture of the two.
[0033] The mass ratio of the originally added solid electrolyte powder particles to the CNTs is 50:50-1:99.
[0034] The frequency of ultrasound is 1-100 kHz, the stirring speed is 5 rpm-50 rpm, and the time is 0.5 hour-5.0 hours.
[0035] In the liquid phase dispersion system, the dispersion liquid is a mixture of one or more of deionized water, N-methylpyrrolidone, alcohol, dimethylformamide, ethyl acetate, and isopropanol.
[0036] Step 130, drying the composite product to obtain a solid electrolyte composite mixed ion conductor material.
[0037] In the above process, the purpose of modifying the solid electrolyte powder particles by a surfactant containing a hydrophobic group is to make the solid electrolyte particles easier to mix and disperse with other materials such as carbon nanotubes (CNTs). During this modification process, the hydrophobic group of the surfactant can interact with the surface of the solid electrolyte particles, making them more compatible and therefore easier to interact with the liquid. This helps to improve the solubility of the solid electrolyte particles and make them better dispersed in the liquid. The modified solid electrolyte particles are easier to disperse in the liquid. The surfactant also acts as a surfactant between the modified solid electrolyte particles and CNTs. This means that they help reduce the surface tension at the solid-liquid interface and promote better mixing of the two materials.
[0038] Ultrasonic action is an important factor when the modified solid electrolyte particles and CNTs are dispersed in a liquid phase dispersion system by ultrasonic stirring. Ultrasonic waves generate high-frequency mechanical waves in the liquid, which mix the materials by generating tiny bubbles and eddies. The action of ultrasound helps to evenly disperse the modified solid electrolyte particles and CNTs in the liquid and promotes the physical and chemical interactions between them. This helps to form a uniform composite product, so that CNTs are evenly dispersed in the modified electrolyte particles.
[0039] The solid electrolyte composite mixed ion conductor material finally prepared by the above preparation method has excellent electrical conductivity and physical properties and is suitable for applications such as high-performance batteries, such as lithium-ion batteries.
[0040] The preparation method of the mixed ion conductor material of the solid electrolyte composite provided by the embodiment of the present invention, by using a surfactant containing a hydrophobic group, the hydrophobic group interacts with the surface of the solid electrolyte particles to reduce the surface tension of the interface, which can improve the compatibility between the components, help disperse the solid electrolyte particles, reduce the agglomeration and accumulation of the particles, and help prepare a uniform mixed material. In addition, the hydrophobic group can also improve the interaction between the solid electrolyte particles and the carbon nanotubes, and promote their dispersion in the liquid phase. By compounding with carbon nanotubes, the conductivity of the battery can be enhanced, while providing a high-strength and chemically stable support.
[0041] The mixed ion conductor material prepared by the present invention can conduct both ions and electrons. The mixed ion conductor material can help inhibit the formation of lithium dendrites because the material has both ion conductivity and electronic conductivity, which makes the current distribution inside the battery more uniform, reduces the formation of dendrites and the problems caused by uneven current inside the battery, thereby ensuring the safe operation of high-capacity lithium batteries, thereby improving the coulomb efficiency and cycle life of all-solid-state lithium batteries.
[0042] In order to more clearly illustrate the purpose and advantages of the present invention, the present invention is further described below in conjunction with the embodiments. In addition, the embodiments described in the present invention are only partial embodiments. Based on the embodiments described in the present invention, all other embodiments obtained by those skilled in the art without creative work are within the protection scope of the present invention. In addition, it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.
[0043] Example 1
[0044] This embodiment provides a preparation process of a solid electrolyte composite mixed ion conductor material, and the specific preparation process is as follows.
[0045] Step 1, using deionized water as the liquid phase system of the dispersion liquid, dispersing sodium dodecyl sulfate surfactant and solid electrolyte lithium lanthanum zirconium oxide with an average particle size of 200nm, modifying the small-particle solid electrolyte lithium lanthanum zirconium oxide with sodium dodecyl sulfate surfactant, and obtaining the modified solid electrolyte particles after drying; the mass ratio of solid electrolyte powder to surfactant is 99:1. The dispersion speed of the dispersion treatment is 1000rpm, the dispersion time is 4h, the drying temperature is 100℃, and the moisture content after drying is less than 5000ppm.
[0046] Step 2, using deionized water as the liquid phase system of the dispersion liquid, the modified solid electrolyte lithium lanthanum zirconium oxide obtained in step 1 and the multi-arm CNTs are mixed and stirred in an ultrasonic device with a frequency of 50 kHz for 1 hour at a mass ratio of 50:50, wherein the stirring speed is 10 rpm.
[0047] Step 3, drying the composite product that is stirred and dispersed uniformly at a drying temperature of 100° C. to obtain the desired solid electrolyte composite mixed ion conductor material.
[0048] Example 2
[0049] This embodiment provides a preparation process of a solid electrolyte composite mixed ion conductor material, and the specific preparation process is as follows.
[0050] Step 1, using deionized water as the liquid phase system of the dispersion liquid, dispersing sodium dodecyl sulfate surfactant and solid electrolyte lithium lanthanum zirconium oxide with an average particle size of 100nm, modifying the small-particle solid electrolyte lithium lanthanum zirconium oxide with sodium dodecyl sulfate surfactant, and obtaining the modified solid electrolyte particles after drying; the mass ratio of solid electrolyte powder to surfactant is 95:5. Among them, the dispersion speed of the dispersion treatment is 1500rpm, the dispersion time is 2h, the drying temperature is 120℃, and the moisture content after drying is less than 5000ppm.
[0051] Step 2, using deionized water as the liquid phase system of the dispersion liquid, mixing the modified solid electrolyte lithium lanthanum zirconium oxide obtained in step 1 with the multi-arm CNTs in a mass ratio of 40:60 in an ultrasonic device with a frequency of 50 kHz for 1 hour, wherein the stirring speed is 20 rpm;
[0052] Step 3, drying the composite product that is stirred and dispersed uniformly at a drying temperature of 100° C. to obtain the desired solid electrolyte composite mixed ion conductor material.
[0053] Example 3
[0054] This embodiment provides a preparation process of a solid electrolyte composite mixed ion conductor material, and the specific preparation process is as follows.
[0055] Step 1, using dimethylformamide as the liquid phase system of the dispersion liquid, dispersing sodium dodecyl sulfate surfactant and solid electrolyte lithium lanthanum zirconium oxide with an average particle size of 200nm, modifying the small-particle solid electrolyte lithium lanthanum zirconium oxide with sodium dodecyl sulfate surfactant, and obtaining the modified solid electrolyte particles after drying; wherein the mass ratio of the solid electrolyte powder to the surfactant is 90:10. The dispersion speed of the dispersion treatment is 1000rpm, the dispersion time is 4h, the drying temperature is 100℃, and the moisture content after drying is less than 5000ppm.
[0056] Step 2, using deionized water as the liquid phase system of the dispersion liquid, the modified solid electrolyte lithium lanthanum zirconium oxide obtained in step 1 and the multi-arm CNTs are mixed and stirred in an ultrasonic device with a frequency of 50 kHz for 1 hour at a mass ratio of 30:70, wherein the stirring speed is 10 rpm.
[0057] Step 3, drying the composite product that is stirred and dispersed uniformly at a drying temperature of 100° C. to obtain the desired solid electrolyte composite mixed ion conductor material.
[0058] Example 4
[0059] This embodiment provides a preparation process of a solid electrolyte composite mixed ion conductor material, and the specific preparation process is as follows.
[0060] Step 1, using deionized water as the liquid phase system of the dispersion liquid, dispersing sodium dodecyl sulfate surfactant and solid electrolyte lithium lanthanum zirconium oxide with an average particle size of 100nm, modifying the small-particle solid electrolyte lithium lanthanum zirconium oxide with sodium dodecyl sulfate surfactant, and obtaining the modified solid electrolyte particles after drying; wherein the mass ratio of the solid electrolyte powder to the surfactant is 85:15. The dispersion speed of the dispersion treatment is 1500rpm, the dispersion time is 2h, the drying temperature is 120℃, and the moisture content after drying is less than 5000ppm.
[0061] Step 2, using deionized water as the liquid phase system of the dispersion liquid, the modified solid electrolyte lithium lanthanum zirconium oxide obtained in step 1 and the multi-arm CNTs are mixed and stirred in an ultrasonic device with a frequency of 50 kHz for 1 hour at a mass ratio of 20:80, wherein the stirring speed is 10 rpm.
[0062] Step 3, drying the composite product that is stirred and dispersed uniformly at a drying temperature of 100° C. to obtain the desired solid electrolyte composite mixed ion conductor material.
[0063] Example 5
[0064] This embodiment provides a preparation process of a solid electrolyte composite mixed ion conductor material, and the specific preparation process is as follows.
[0065] Step 1, using N-methylpyrrolidone as the liquid phase system of the dispersion liquid, dispersing sodium dodecylbenzenesulfonate surfactant and solid electrolyte lithium lanthanum zirconium oxide with an average particle size of 250nm, modifying small-particle solid electrolyte lithium aluminum titanium phosphate with sodium dodecyl sulfate surfactant, and drying to obtain modified solid electrolyte particles; wherein the mass ratio of solid electrolyte powder to surfactant is 90:10. The dispersion speed of the dispersion treatment is 1000rpm, the dispersion time is 4h, the drying temperature is 100℃, and the moisture content after drying is less than 5000ppm.
[0066] Step 2, using N-methylpyrrolidone as the liquid phase system of the dispersion liquid, the modified solid electrolyte lithium lanthanum zirconium oxide obtained in step 1 and the multi-arm CNTs are mixed and stirred in an ultrasonic device with a frequency of 50 kHz for 1 hour at a mass ratio of 50:50, wherein the stirring speed is 10 rpm.
[0067] Step 3, drying the composite product that is stirred and dispersed uniformly at a drying temperature of 100° C. to obtain the desired solid electrolyte modified CNTS ion-conducting and high-conductivity electronic material.
[0068] Example 6
[0069] This embodiment provides a preparation process of a solid electrolyte composite mixed ion conductor material, and the specific preparation process is as follows.
[0070] Step 1, using deionized water as the liquid phase system of the dispersion liquid, dispersing sodium tridecyl sulfosuccinate surfactant and solid electrolyte lithium lanthanum zirconium oxide with an average particle size of 200 nm, and modifying the small-particle solid electrolyte lithium lanthanum zirconium oxide with sodium tridecyl sulfosuccinate surfactant, the mass ratio of the solid electrolyte powder to the surfactant is 90:10; wherein, the dispersion speed of the dispersion treatment is 1000 rpm, the dispersion time is 4 hours, the drying temperature is 100°C, and the moisture content after drying is less than 5000 ppm.
[0071] Step 2, using deionized water as the liquid phase system of the dispersion liquid, the modified solid electrolyte lithium lanthanum zirconium oxide obtained in step 1 and the multi-arm CNTs are mixed and stirred in an ultrasonic device with a frequency of 50 kHz for 1 hour at a mass ratio of 50:50, wherein the stirring speed is 10 rpm.
[0072] Step 3, drying the composite product that is stirred and dispersed uniformly at a drying temperature of 100° C. to obtain the desired solid electrolyte composite mixed ion conductor material.
[0073] Example 7
[0074] This embodiment provides a preparation process of a solid electrolyte composite mixed ion conductor material, and the specific preparation process is as follows.
[0075] Step 1, using deionized water as the liquid phase system of the dispersion liquid, dispersing sodium dodecyl sulfate surfactant and solid electrolyte lithium titanium silicate with an average particle size of 100 nm, modifying the solid electrolyte lithium titanium silicate with a small particle size with sodium dodecyl sulfate surfactant, and obtaining modified solid electrolyte particles after drying; the mass ratio of the solid electrolyte powder to the surfactant is 90:10; wherein, the dispersion speed of the dispersion treatment is 1500rpm, the dispersion time is 2h, the drying temperature is 120°C, and the moisture content after drying is less than 5000ppm.
[0076] Step 2, using deionized water as the liquid phase system of the dispersion liquid, the modified solid electrolyte lithium titanium silicate obtained in step 1 and the multi-arm CNTs are mixed and stirred in an ultrasonic device with a frequency of 50 kHz for 1 hour at a mass ratio of 40:60, wherein the stirring speed is 10 rpm.
[0077] Step 3, drying the composite product that is stirred and dispersed uniformly at a drying temperature of 100° C. to obtain the desired solid electrolyte composite mixed ion conductor material.
[0078] Example 8
[0079] This embodiment provides a preparation process of a solid electrolyte composite mixed ion conductor material, and the specific preparation process is as follows.
[0080] Step 1, using dimethylformamide as the liquid phase system of the dispersion liquid, dispersing sodium dodecyl sulfate surfactant and solid electrolyte lithium lanthanum zirconium oxide with an average particle size of 500nm, modifying the small-particle solid electrolyte lithium lanthanum zirconium oxide with sodium dodecyl sulfate surfactant, and obtaining modified solid electrolyte particles after drying; the mass ratio of the solid electrolyte powder to the surfactant is 85:15; wherein, the dispersion speed of the dispersion treatment is 2000rpm, the dispersion time is 4h, the drying temperature is 90°C, and the moisture content after drying is less than 5000ppm.
[0081] Step 2, using deionized water as the liquid phase system of the dispersion liquid, the modified solid electrolyte lithium lanthanum zirconium oxide obtained in step 1 and the single-arm CNTs are mixed and stirred in an ultrasonic device with a frequency of 50 kHz for 1 hour at a mass ratio of 50:50, wherein the stirring speed is 10 rpm.
[0082] Step 3, drying the composite product that is stirred and dispersed uniformly at a drying temperature of 100° C. to obtain the desired solid electrolyte modified CNTS ion-conducting and high-conductivity electronic material.
[0083] Comparative Example 1
[0084] This comparative example provides a preparation process of a solid electrolyte composite material, and the specific preparation process is as follows.
[0085] Step 1: Using deionized water as the liquid phase system of the dispersion liquid, the solid electrolyte lithium lanthanum zirconium oxide and the multi-arm CNTs are mixed and stirred in an ultrasonic device with a frequency of 50 kHz for 1 hour at a mass ratio of 50:50, wherein the stirring speed is 10 rpm.
[0086] Step 2, drying the composite product that is stirred and dispersed uniformly, with the drying temperature being 100° C., to obtain the desired solid electrolyte composite material.
[0087] Comparative Example 2
[0088] This comparative example provides a preparation process of a modified solid electrolyte material, and the specific preparation process is as follows.
[0089] Step 1, using deionized water as the liquid phase system of the dispersion liquid, dispersing sodium dodecyl sulfate surfactant and solid electrolyte lithium lanthanum zirconium oxide with an average particle size of 200nm, modifying the small-particle solid electrolyte lithium lanthanum zirconium oxide with sodium dodecyl sulfate surfactant, and obtaining the modified solid electrolyte particles after drying; the mass ratio of solid electrolyte powder to surfactant is 99:1. The dispersion speed of the dispersion treatment is 1000rpm, the dispersion time is 4h, the drying temperature is 100℃, and the moisture content after drying is less than 5000ppm.
[0090] The materials obtained from the above embodiments and comparative examples were used for testing.
[0091] The battery assembly method is as follows: using the solid electrolyte composite mixed ion conductor material prepared in the above embodiments as a positive electrode additive, the amount used is 2% of the positive electrode mass, and assembling a lithium ion battery in a glove box filled with Ar atmosphere by conventional methods, wherein lithium cobalt oxide is used as the positive electrode and lithium metal is used as the negative electrode; and evaluating its electrochemical performance by testing. The test conditions are as follows: the test battery is placed on the test instrument in a test environment of 30°C, the charge and discharge current is 0.1A / g, the charge cut-off voltage is 4.5V, and the discharge cut-off voltage is 3.0V.
[0092] In order to verify the electrochemical stability of the mixed ion conductor material composited with the solid electrolyte, the button cell was disassembled after 100 cycles to obtain the corresponding pole piece and the expansion rate of the pole piece was obtained based on the change in thickness of the pole piece before and after the cycle test.
[0093] The test results are shown in Table 1.
[0094]
[0095] Table 1
[0096] By comparing the above test data, it can be seen that the method for preparing the solid electrolyte composite mixed ion conductor material provided by the embodiment of the present invention has a higher specific capacity and 100-cycle capacity retention rate, and the expansion rate of the pole piece is also lower.
[0097] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a solid electrolyte composite mixed ion conductor material, characterized in that: The preparation method comprises: In a liquid phase dispersion system, a surfactant containing a hydrophobic group and solid electrolyte powder particles are dispersed, the solid electrolyte powder particles are modified by the surfactant containing a hydrophobic group, and the modified solid electrolyte particles are obtained after drying; The modified solid electrolyte particles and carbon nanotubes (CNTs) are dispersed by ultrasonic stirring in a liquid phase dispersion system to obtain a composite product; The composite product is dried to obtain the solid electrolyte composite mixed ion conductor material.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the solid electrolyte powder particles to the surfactant is 99:1-85:15; The mass ratio of the solid electrolyte powder particles to the CNTs is 50:50-1:
99.
3. The preparation method according to claim 1, characterized in that: The dispersion speed of the dispersion treatment is 1000-3000 rpm, the dispersion time is 0.5-4h, the drying temperature is 90-200°C, and the moisture content after drying is less than 5000ppm.
4. The preparation method according to claim 1, characterized in that: The frequency of the ultrasound is 1-100 kHz, the stirring speed is 5 rpm-50 rpm, and the time is 0.5 hour-5.0 hours.
5. The preparation method according to claim 1, characterized in that: The solid electrolyte powder particles are crystalline materials containing lithium or sodium, and the particle size is between 10nm-1um.
6. The preparation method according to claim 1, characterized in that: The solid electrolyte powder particles specifically include: lithium lanthanum zirconium oxide, lithium lanthanum niobium oxide, lithium lanthanum tantalum oxide, lithium titanium silicate, lithium aluminum titanium phosphate, lithium lanthanum titanium oxide, lithium aluminum titanium oxide, lithium zirconium phosphate, lithium zinc phosphate, lithium calcium tannin oxide, lithium zirconium silicate, sodium zirconium silicon phosphorus oxide, sodium iron copper manganese oxide, β-aluminum oxide or a mixture of one or more; The surfactant containing a hydrophobic group specifically includes: sodium tridecyl sulfosuccinate, polyoxyethylene oleate, hydroxyethyl ether cellulose, octadecylamine, sodium dodecyl sulfate, dodecylamine, sodium dodecylbenzene sulfonate, siloxane coupling agent, phthalate coupling agent, aluminate coupling agent, metal composite coupling agent, phosphate coupling agent, borate coupling agent, etc., including alkane groups, cycloalkane groups, aromatic hydrocarbon groups, fatty acid groups, polyoxypropylene groups, and one or more mixtures of coupling agents.
7. The preparation method according to claim 1, characterized in that: In the liquid phase dispersion system, the dispersion liquid is a mixture of one or more of deionized water, N-methylpyrrolidone, alcohol, dimethylformamide, ethyl acetate, and isopropanol.
8. The preparation method according to claim 1, characterized in that: The CNTs include single-arm CNTs and multi-arm CNTs, or a mixture of the two.
9. A solid electrolyte composite mixed ion conductor material prepared by the preparation method described in any one of claims 1 to 8.
10. A lithium ion battery comprising the solid electrolyte composite mixed ion conductor material according to claim 9.